Evaluation of the Efficacy and Feasibility of a Telerehabilitation Program Using Language and Cognitive Exercises in Multi-Domain Amnestic Mild Cognitive Impairment. (24th September 2022) - Nousia, Anastasia; Pappa, Evangelia; Siokas, Vasileios; Liampas, Ioannis; Tsouris, Zisis; Messinis, Lambros; Patrikelis, Panayiotis; Manouilidou, Christina; Dardiotis, Efthimios; Nasios, Grigorios
Abstract: Objective: The aim of the present study was to investigate the efficacy and feasibility of a telerehabilitation program in multi-domain amnestic Mild Cognitive Impairment (md-aMCI). The study sample consisted of 30 patients with md-aMCI and aged 60–80 years. Methods: The participants were randomly divided into two groups. The Training Group (TG), which received cognitive training by using the RehaCom software as well as paper-pencil language training and the Control Group (CG) which received standard clinical care (e.g., psychotherapy or/and physiotherapy). Duration of the telerehabilitation intervention was 15 weeks (twice a week for 60 min/session). Results: Our results revealed that the neuropsychological performance of the TG group after the telerehabilitation intervention improved on a statistically significant level on the domains of delayed and working memory, confrontation naming, verbal fluency, and global cognition. Comparison between the TG and CG revealed a significant impact of the telerehabilitation program on the domains of memory (delay and working) and language (naming and verbal fluency) as well as global cognition performance. Conclusion: The findings of the study are promising in that the telerehabilitation intervention appears to be a useful method in improving or stabilizing cognitive decline in md-aMCI individuals and was a particularly effective alternative approach during the period of the pandemic lockdown. Specifically, the beneficial impact of the telerehabilitation intervention on episodic memory (which is one of the first domains to show impairment in md-aMCI patients) provides us with hope and evidence that these types of interventions may be applied with similar success using face-to-face interventions.